Pan-Cancer Analysis of PARP1 Alterations as Biomarkers in the Prediction of Immunotherapeutic Effects and the Association of Its Expression Levels and Immunotherapy Signatures - Zhang, Xinke; Wang, Yingying; A, Gari; Qu, Chunhua; Chen, Jiewei (Frontiers in Immunology, 2021)
Background: Comprehensive analysis of the predictive values of PARP1 alteration for ICI effectiveness in tumors remains unclear, and the association between its expression and immunotherapy signatures, needs to be explored further. Methods: We performed some analyses with the cBioPortal online database, TIMER2.0 and TCGA database. Several analyses were performed using R, version 3.6.3 (http://www.r-project.org/). Results: We found that PARP1 alteration was associated with markedly higher tumor mutation burden (TMB) levels in a variety of tumors (P < 0.01). Impressively, patients with PARP1 alterations in advanced tumors showed better overall survival (OS) in the ICI-treated cohort (P = 0.016). PARP1 altered group was substantially correlated with higher immune infiltrates across most tumors (P < 0.05). The PARP1 altered group showed high expression in transcription (P < 0.001), and higher expression of LAG3, PDCD1, CTLA-4, and TIGIT (P < 0.05). Higher PARP1 expression had a worse OS in several tumors (P < 0.05). Further, high PARP1 expression was significantly associated with six immune cells (B cells, CD4+ T cells, CD8+ T cells, macrophages, neutrophils, and dendritic cells) in most tumors, including COAD, HNSC, KIRC and LIHC (P < 0.05). and PARP1 expression was significantly positively correlated with the transcription levels of some of the 47 immune checkpoint genes, such as CD274, CTLA4, and PDCD1 in several tumors, including PAAD, LIHC, KIRC, HNSC, and BLCA (P < 0.05). A significant positive association between PARP1 expression and the number of immune neoantigen was found within COAD, KIRC, LUAD, PAAD and THYM (P < 0.05), and there were also significantly positive correlations between PARP1 expression and TMB in many tumors like ACC, COAD, KICH, LGG, LUAD, READ, SKCM and STAD (P < 0.05). In addition, high PARP1 expression was positively associated with microsatellite instability event in COAD, KIRP, BRCA, GBM, LUSC, LGG, READ, UCEC, SKCM and LUAD (P < 0.05). Conclusions: Our results highlight the significance of PARP1 alterations as pan-cancer predictive biomarkers for ICI treatment, and its expression levels seem to be correlated with immunotherapy-associated signatures, thus may be a promising biomarker for predicting ICI response in several tumors.